Impact of financial development on inclusive growth in Nigeria (Journal of Economic Research & Business Administration, 2022)
This study examined the impact of financial development on inclusive growth in Nigeria using a timeseries data obtained from secondary sources between 1999 and 2019. Financial development was measuredusing broad money supply and domestic credit to private sector, while inclusive growth was measuredfrom income perspective using per capita GDP and from expenditure perspective using householdconsumption expenditure. The data were mainly obtained from World Development Indicators data basefor various years. The data were analysed using Autoregressive Distributed Lag Bound test approach. Theresults of the ARDL revealed that financial development proxy with broad money supply exert significantpositive impact on per capita income and household consumption expenditure in both short and long run.On the contrary, domestic credit to private sector has significant negative impact on per capita income inshort and long run while the impact on household consumption expenditure was not significant in bothshort and long run. The study therefore recommends that the government can use broad money supply asone of the financial development instruments to promote inclusive growth in Nigeria. in addition, attentionshould be paid to the allocation of funds to private sector and the efficiency of such fund in order to reverseunproductive impact of fund allocated to private sector on inclusive growth in Nigeria.Key words: inclusive growth, financial development, trade openness, broad money supply.